1998
DOI: 10.1063/1.475680
|View full text |Cite
|
Sign up to set email alerts
|

Radial and orientational solvation structure of the sodium chloride ion pair in dimethyl sulfoxide

Abstract: The structures of the solvation shells around each ion of the Na ϩ -Cl Ϫ ion pair in liquid dimethyl sulfoxide ͑DMSO͒ have been studied in terms of the ion-solvent radial distribution functions ͑RDFs͒ and the ion-solvent orientational distribution functions ͑ODFs͒ at the three interionic separations of 2.6 Å, 4.9 Å, and 7.2 Å. The solvation shell around the sodium ion consists of only three DMSO molecules at the ion-ion separation of 2.6 Å and this number grows to five DMSO molecules at interionic separation 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…It may be that the optically induced electron transfer which moves charge away from the iron also causes the sodium counterion to move far enough away from the complex to allow a solvent molecule to occasionally slip into the void. The characteristic time for solvent-separated ion pair to reconvert to an ion pair is expected to be nanoseconds or longer. , …”
Section: Discussionmentioning
confidence: 99%
“…It may be that the optically induced electron transfer which moves charge away from the iron also causes the sodium counterion to move far enough away from the complex to allow a solvent molecule to occasionally slip into the void. The characteristic time for solvent-separated ion pair to reconvert to an ion pair is expected to be nanoseconds or longer. , …”
Section: Discussionmentioning
confidence: 99%
“…[28] A variety of theoretical and experimental studies on liquid DMSO, [30][31][32][33][34] water/DMSO mixtures, [35][36][37][38][39][40] DMSO/nonaqueous electrolyte solutions [41,42] and solutions of biomolecules in DMSO [43][44][45] have been performed in recent years to understand the physical properties of DMSO solutions. Solutions of alkalimetal ions, mostly Li + , in DMSO have also been investigated experimentally [46][47][48][49] and theoretically, [41,[50][51][52][53] as well as in water/ DMSO mixtures [54][55][56] and in other solvent combinations. [57][58][59] One of the first reports on the utilisation of 7 Li NMR in the investigation of LiClO 4 in various solvents (including DMSO) was published by Maciel et al [88] In DMSO, no evidence for contact ion pairing was observed [56,60] as might be expected, for instance, in THF (DN = 7.4).…”
Section: Introductionmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) is an important industrial solvent and is widely used in chemistry and biology because of its unique solvent properties 1, 2. In the past few years, there have been numerous studies on aqueous3–24 and nonaqueous25–30 mixtures containing DMSO. DMSO–chloroform mixtures have been found to show interesting nonideal behavior in their thermodynamic31–36 and spectral41, 42 properties with variation of composition.…”
Section: Introductionmentioning
confidence: 99%